174k views
4 votes
What is the solution to 4(x-1)-2(3x+5)=-3x-1

2 Answers

3 votes
4 (x-1)-2 (3x+5)=-3x-1
4x-4-6x-10=-3x-1 Distribute.
-2x -14= -3x-1 Combine like terms.
-14 = -x -1 Add 2x to both sides.
-13 = -x Add 1 to both sides to get x alone.
13 = x Divide both sides by -1 to get x positive and you habe your answer.

x=13
User JordanBean
by
5.2k points
5 votes

To solve this problem, we need to get the variable x alone on one side of the equation. To begin, we are going to use the distributive property twice on the left side of the equation to expand the multiplication and get rid of the parentheses.

4(x-1) - 2(3x + 5) = -3x -1

4x - 4 -6x - 10 = -3x - 1

Next, we should combine like terms on the left side of the equation. This means we should add/subtract the variable terms and the constant terms in order to simplify this equation further.

-2x - 14 = -3x - 1

Then, we have to add 3x to both sides of the equation to get the variable terms all on the left side of the equation.

x - 14 = -1

After that, we should add 14 to both sides of the equation to get the variable x alone one the left side of the equation.

x = 13

Therefore, the answer is 13.

Hope this helps!

User Tom Prats
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.